ANALISIS SEGMENTASI PASAR WISATAWAN MANCANEGARA YANG BERKUNJUNG KE BALI DARI ASPEK SOSIO-EKONOMI DEMOGRAFI, PSIKOGRAFI, DAN PERILAKU - Sandy Br. Ginting, May; Kusuma Negara, I Made; Sudiarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata), 2015)
Tourists visiting Bali diverse and consists of various nationalities. In this case the purpose of segmentation is done in order to target the right market to serve customers better and improve the name of Bali as a tourist destination. As for the more specific purpose, among others, to increase sales, improve market share, communication and promotion and strengthening the image. In this case the segmentation analysis is helpful to understand the needs and desires of purchasing power (needs, wants, and purchasing power). The purpose of this study was to determine differences in behavior, desires and lifestyles of foreign tourists visiting Bali. In conducting the survey questionnaire with a number of researchers spread respondent 138 people were divided on several continents, namely 54 respondents from Europe, 32 respondents from Asia, 30 respondents from Australia and 22 respondents from America. In this study data analysis using SPSS(statistical package for social science) version 20 with Microsoft Excel. The result showed that differences are significant third against segmentation surveyed: segmentation socio-economic demographic, psychographic, and behavior by continent. Travelers who originated from Europe prefer cultural tourism and stayed ? 6 days, travelers from Australia prefer beach activities and stayed more than 2 weeks, travelers from America also prefer beach activities and stayed ? 6 days, but Asia travelers showed they prefer Adventures activities when they visited Bali and stayed ? 6 days .
Keywords: Segmentation, Foreign Tourist, Socio-Economic